(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the first part of his autobiography, entitled Words,Jean-Paul Sartre describes how as a child he discovered that words gave him asense of power and a control of a world from which he felt divorced, and how hedeveloped the habit of adopting personae to cope with reality. But this, hewrote, gave a pattern to his adult life and led to difficulty in coming toterms with his own personality and its emotional needs. Two concepts wereimportant in Sartre’s thought: one wasalienation and the other angst. In his autobiography he gives these a personalreference. Alienation was concerned with his difficulty of dealing withreality, and angst with the anxiety and fear his emotions evoked. Words forSartre were a means of dealing with these; they provided what the psychiatristscall a defensive mechanism.